Efektivitas Penggunaan Google Classroom untuk Meningkatkan Keaktifan Belajar Siswa - Gita Supriatini (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2022)
The Covid-19 pandemic requires teachers to be more creative and not technologically stuttering. One of the learning media is Google Classroom. The subjects of this study were members of Student SDN Kebalen 07 Bekasi. Google Classroom is intended to help all areas of education help students to find or overcome learning difficulties, share lessons and create assignments without having to attend class. The research stages that will be carried out are adjusted to the stages of Class Action Research (PTK).At the planning stage, namely with the discovery of problems that occur during online learning, teachers review core competencies and basic competencies, study materials, breastfeed RPP, prepare media and prepare evaluation tools.The second stage is the action of making the group do the bullying guidance in class using google clasroom is to display material, explain it and do A&A, to work on quizzes using the application Next observe the executor. The next stage is to reflect on the actions that take place in the cycle to plan the next action.The purpose of this study is to improve and improve quality. Research is carried out to overcome students who get lectures in learning in the field of study Indonesian. With the learning model that has turned into online, then with this research, it can encourage students to be more active in learning and improve maximum learning outcomes with the same characteristics relatively the same can implement student learning strategies more effectively.